O potrzebie zachowania "narady" przy orzekaniu w sprawach karnych - Grzęda, Ewa (PRAWO i WIĘŹ, 2026)
The presented article addresses the significance of the reflective phase in criminal proceedings. It acknowledges the prevailing consensus in legal scholarship and jurisprudence, which assumes the necessity of deliberation before issuing a judgment. While this viewpoint is undoubtedly valid, it is difficult to overlook the fact that adjudication is usually carried out by single-judge panels. The aim of this study is to propose desirable and universal solutions both in terms of the conceptual framework used to describe the reflective phase of ruling in criminal cases and the need to maintain formalized normative solutions in this regard.